2021
DOI: 10.3390/jcm10204746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Lockdown on Weight, Body Composition, and Behavior of Children, Adolescents, and Young Adults with Prader–Willi Syndrome

Abstract: To reduce transmission of the coronavirus disease 2019 (COVID-19), many countries implemented lockdowns, causing the closure of childcare services. This study was designed to evaluate the impact of the COVID-19 lockdown in March–April 2020 on children, adolescents, and young adults with Prader–Willi syndrome (PWS) living in Germany. We recruited 180 participants with a genetically confirmed PWS. All families completed a questionnaire, and participants underwent a post-lockdown assessment; the last examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This would be consistent with the observation of levels of treatment initiations raising back to the expected in the post-lockdown period, where such decrease in cardiovascular event was no longer observed. However, a similar hypothesis would appear unlikely regarding antidiabetic drugs, for which initiations were found both importantly decreased during lockdown and persistently decreased afterwards despite numerous publications documented that lockdown had been associated with increase in sedentariness and weight gains [ 35 37 ]. Regarding diabetes mellitus management, it also suggests that the lockdown might have resulted in altering the overall health prognosis of some patients over the period because of these lacks of treatment continuity of optimization and that an excess amount of outcome relating to these phenomenons might have already occurred or will be observed in the coming months.…”
Section: Discussionmentioning
confidence: 99%
“…This would be consistent with the observation of levels of treatment initiations raising back to the expected in the post-lockdown period, where such decrease in cardiovascular event was no longer observed. However, a similar hypothesis would appear unlikely regarding antidiabetic drugs, for which initiations were found both importantly decreased during lockdown and persistently decreased afterwards despite numerous publications documented that lockdown had been associated with increase in sedentariness and weight gains [ 35 37 ]. Regarding diabetes mellitus management, it also suggests that the lockdown might have resulted in altering the overall health prognosis of some patients over the period because of these lacks of treatment continuity of optimization and that an excess amount of outcome relating to these phenomenons might have already occurred or will be observed in the coming months.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies who investigated the lockdown influence on populations other than children with DS. Chang et al [ 17 ] and Mohr et al [ 18 ] reported that containments led to reduced physical activities and excess food consumption, weight gain, and behavioral disorders. The participants in this study manifested variable comorbidities, microcephaly, growth retardation, or obesity which were detected by anthropometric measures.…”
Section: Discussionmentioning
confidence: 99%
“…This scale is designed to measure existential feelings and perceptions. Respondents had to answer on a 10-point Likert scale, I completely disagree from (1) to I completely agree (10) that "my financial situation has deteriorated due to the COVID-19 crisis".…”
Section: Methodsmentioning
confidence: 99%
“…Protective measures include social exclusion, closure of educational institutions, restrictions on events and social gatherings, regulations on the use of personal protective equipment (especially masks), travel restrictions, border closures and ongoing testing [6][7][8]. In addition, some nations have declared a state of emergency and introduced a partial lockdown to control the current third wave [9,10], which has restricted the movement of people and thus has an impact on the world of work [11][12][13]. Working from home is becoming more widespread in the world [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%